PATH-38. ROSETTE-FORMING GLIONEURONAL TUMOR IS DEFINED BY FGFR1 ACTIVATING ALTERATIONS WITH FREQUENT ACCOMPANYING PI3K AND MAPK PATHWAY MUTATIONS. (11th November 2019) - Calixto-Hope, Lucas; Lee, Julieann; Sloan, Emily; Hofmann, Jeffrey; Van Ziffle, Jessica; Onodera, Courtney; Grenert, James; Devine, Patrick; Kline, Cassie; Banerjee, Anu; Clarke, Jennifer; Taylor, Jennie; et al.
Abstract: BACKGROUND: Rosette-forming glioneuronal tumor (RGNT) is an uncommon CNS tumor originally described in the fourth ventricle characterized by a low-grade glial neoplasm admixed with a rosette-forming neurocytic component. METHODS: We reviewed clinicopathologic features of 42 patients with RGNT. Targeted next-generation sequencing was performed, and genome-wide methylation profiling is underway. RESULTS: The 20 male and 22 female patients had a mean age of 25 years (range 3–47) at time of diagnosis. Tumors were located within or adjacent to the lateral ventricle (n=16), fourth ventricle (15), third ventricle (9), and spinal cord (2). All 31 tumors assessed to date contained FGFR1 activating alterations, either in-frame gene fusion, kinase domain tandem duplication, or hotspot missense mutation in the kinase domain (p.N546 or p.K656). While 7 of these 31 tumors harbored FGFR1 alterations as the solitary pathogenic event, 24 contained additional pathogenic alterations within PI3-kinase or MAP kinase pathway genes: 5 with additional PIK3CA and NF1 mutations, 4 with PIK3CA mutation, 3 with PIK3R1 mutation (one of which also contained focal RAF1 amplification), 5 with PTPN11 mutation (one with additional PIK3R1 mutation), and 2 with NF1 deletion. The other 5 cases demonstrated anaplastic features including hypercellularity and increased mitotic activity. Among these anaplastic cases, 3 harbored inactivating ATRX mutations and two harbored CDKN2A homozygous deletion, in addition to the FGFR1 alterations plus other PI3-kinase and MAP kinase gene mutations seen in those RGNT without anaplasia. CONCLUSION: Independent of ventricular location, RGNT is defined by FGFR1 activating mutations or rearrangements, which are frequently accompanied by mutations involving PIK3CA, PIK3R1, PTPN11, NF1, and KRAS . Whereas pilocytic astrocytoma and ganglioglioma are characterized by solitary activating MAP kinase pathway alterations (e.g. BRAF fusion or mutation), RGNT are genetically more complex with dual PI3K-Akt-mTOR and Ras-Raf-MAPK pathway activation. Rare anaplastic examples may show additional ATRX and/or CDKN2A inactivation.